2022
DOI: 10.3390/ma15124335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impurities on the Process of Obtaining Calcium Carbonate during the Processing of Phosphogypsum

Abstract: The article is devoted to the study of the influence of residual sulfuric and phosphoric acids on the process of processing large-tonnage phosphogypsum (PG) waste into calcium carbonate. In the Russian Federation, about 10 percent of existing phosphogypsum waste is processed into construction materials. Acidic impurities (phosphoric and sulfuric acids) in their composition are an obstacle to the use of phosphogypsum for the production of binders. This study finds that impurities also reduce the chemical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…where k is the cryoscopic constant of benzene (5.12 • C), a is the asphaltene concentration in grams per 1000 g of solvent, ∆T is the freezing point depression. The elemental composition of asphaltenes was determined on a LECO CHN628 analyzer (Leco Corporation, St. Joseph, MI, USA) [50,51], the sulfur content was determined on an XRF-1800 (Shimadzu, Japan) X-ray fluorescence analyzer [52,53]. The oxygen content was calculated by subtraction the total content of other elements from 100%.…”
Section: Asphaltenes and Solvents Characterizationmentioning
confidence: 99%
“…where k is the cryoscopic constant of benzene (5.12 • C), a is the asphaltene concentration in grams per 1000 g of solvent, ∆T is the freezing point depression. The elemental composition of asphaltenes was determined on a LECO CHN628 analyzer (Leco Corporation, St. Joseph, MI, USA) [50,51], the sulfur content was determined on an XRF-1800 (Shimadzu, Japan) X-ray fluorescence analyzer [52,53]. The oxygen content was calculated by subtraction the total content of other elements from 100%.…”
Section: Asphaltenes and Solvents Characterizationmentioning
confidence: 99%
“…The carbonate conversion of phosphogypsum is less demanding on raw materials, while it is possible to process phosphogypsum of any lying state. The potential of phosphorus feedstock for recovery of REE is described in the works [10,11]. REE in red mud are associated with iron minerals [12,13]; thus, the process is more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Pyagai et al [24] studied the waste phosphogypsum from the Phosagro industrial site (Volkhov), which is a gray-white powder with a mass fraction of 60% of the main substance in terms of calcium sulfate. The study found that acidic impurities (phosphoric and sulfuric acids) in the phosphogypsum are an obstacle to its use in the production of building materials.…”
Section: Introductionmentioning
confidence: 99%